The Molecular and Cellular Basis of Taste Coding in the Legs of Drosophila - Ling, Frederick (Society for Neuroscience, 2014)
To understand the principles of taste coding, it is necessary to understand the functional organization of the taste organs. Although the labellum of the Drosophila melanogaster head has been described in detail, the tarsal segments of the legs, which collectively contain more taste sensilla than the labellum, have received much less attention. We performed a systematic anatomical, physiological, and molecular analysis of the tarsal sensilla of Drosophila. We construct an anatomical map of all five tarsal segments of each female leg. The taste sensilla of the female foreleg are systematically tested with a panel of 40 diverse compounds, yielding a response matrix of ∼500 sensillum–tastant combinations. Six types of sensilla are characterized. One type was tuned remarkably broadly: it responded to 19 of 27 bitter compounds tested, as well as sugars; another type responded to neither. The midleg is similar but distinct from the foreleg. The response specificities of the tarsal sensilla differ from those of the labellum, as do n-dimensional taste spaces constructed for each organ, enhancing the capacity of the fly to encode and respond to gustatory information. We examined the expression patterns of all 68 gustatory receptors (Grs). A total of 28 Gr–GAL4 drivers are expressed in the legs. We constructed a receptor-to-sensillum map of the legs and a receptor-to-neuron map. Fourteen Gr–GAL4 drivers are expressed uniquely in the bitter-sensing neuron of the sensillum that is tuned exceptionally broadly. Integration of the molecular and physiological maps provides insight into the underlying basis of taste coding.